Superfine nanometer silicon-based negative electrode material prepared based on in-situ high-temperature phase change in confinement microcavity and preparation method thereof

Ultrafine nano-silicon-based anode material is prepared by in-situ high-temperature phase change technology in the confined microcavity, which solves the problem of volume expansion and poor conductivity of silicon-based anode materials in lithium-ion batteries, and achieves high energy density and cycling stability. Simplifies the preparation process and reduces costs.

CN119170777AActive Publication Date: 2024-12-20SUZHOU XRISE NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411432851.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-20
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based anode material in lithium-ion batteries during charging and discharging leads to problems such as mechanical stress, poor conductivity and low Coulomb efficiency, and traditional preparation technology is costly and unstable.

Method used

Using in-situ high-temperature phase change technology in the confined microcavity, silicon is mixed with conductive porous materials, and closed microcavity is constructed through a cladding layer. Transient heating is used to rapidly sublimate and condense into ultrafine nanoparticles, and porous conductive materials are embedded. In this case, a stable structure is formed.

Benefits of technology

It improves the structural stability and cycle life of the material, enhances the cycle stability and electrochemical performance of the battery, reduces production costs, and avoids the use of silane gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170777A_ABST
    Figure CN119170777A_ABST
Patent Text Reader

Abstract

The invention provides a superfine nano silicon-based negative electrode material prepared based on in-situ high-temperature phase change in a specific confinement microcavity and a preparation method of the superfine nano silicon-based negative electrode material. The method comprises the following steps: mixing silicon and a conductive porous material in a solvent, sanding, forming solid particles through reforming granulation, and constructing a confinement microcavity through coating treatment. And the silicon source is sublimated and desublimated into particles with the particle size of less than 10nm through transient heating and cooling, and the particles are embedded into the porous material, so that the extreme nanocrystallization of silicon is realized. The method effectively solves the problems of volume expansion, low conductivity, poor cycle stability and the like when silicon is used as a lithium ion battery negative electrode material, improves the electron transmission and cycle life, simplifies the process, reduces the cost, and has a good commercialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of negative electrode materials for lithium-ion batteries, and specifically relates to an ultrafine nano silicon-based negative electrode material prepared based on in-situ high-temperature phase change in a confined microcavity and a preparation method thereof. Background Art

[0002] In the past three decades, lithium-ion batteries have achieved great commercial success with their high energy density, low self-discharge rate, long cycle life, and light weight. At present, the lithium-ion battery industry is still maintaining rapid growth and is widely used in consumer electronics, new energy vehicles, and energy storage devices. At present, graphite is still the mainstream negative electrode material for lithium-ion batteries, but the theoretical specific capacity of traditional graphite electrodes is only 372mAh / g, which is close to the theoretical capacity ceiling, severely limiting the energy density of lithium-ion batteries and hindering their further improvement.

[0003] Compared with traditional graphite negative electrode materials, the theoretical specific capacity of silicon is as high as 4200mAh / g, which is 11.3 times that of graphite. Therefore, silicon-based negative electrode materials have higher energy density potential. In addition, the lithium deintercalation potential of silicon-based negative electrodes (0.4Vvs.Li / Li + ) is slightly higher than graphite (0.05Vvs.Li / Li +), thus avoiding the surface lithium precipitation phenomenon that may occur during charging. In addition, silicon is widely available, relatively low in cost, non-toxic and pollution-free. Compared with other negative electrode materials, silicon-based negative electrode materials are more competitive. However, during the charging and discharging process, the volume expansion rate of silicon is extremely high (about 300%). This drastic volume change will not only cause repeated cracking of silicon, but also cause silicon to lose its conductive connection with the electrode, resulting in mechanical pulverization and cracking. Repeated volume changes will cause repeated reconstruction and growth of the solid electrolyte interface layer (SEI). Silicon nano-sizing can quickly relax stress, improve the fracture resistance of silicon, and to a certain extent alleviate the mechanical stress generated by silicon during the lithiation process. Nano silicon has the advantages of short lithium ion diffusion distance, large surface area and fast grain boundary transmission. However, when the specific surface area of ​​the silicon-based negative electrode is larger, the specific surface area of ​​the SEI film formed will also be larger, thereby consuming more lithium ions and reducing the first coulomb efficiency of the whole battery. In addition, nano-silicon is easy to agglomerate, which increases the transmission distance of lithium ions. In addition, its poor conductivity makes it unstable after nano-sizing, which easily leads to problems such as fast capacity decay, low coulombic efficiency, poor conductivity, and low reversible capacity, which seriously limits its application in negative electrode materials of lithium-ion batteries. In order to solve the above problems, the current main research direction is to combine it with other matrix materials, and some important progress has been made. Other matrices mainly involve carbon-based materials. The high conductivity of carbon-based materials improves the conductivity of the entire electrode. The porous structure of carbon-based materials can buffer the drastic volume expansion of nano-silicon. At the same time, a stable chemical bond is formed between the atoms in the carbon-based materials and the nano-silicon, forming a stable SEI, which improves the battery specific capacity, cycle stability and first coulombic efficiency.

[0004] At present, the typical preparation technologies of silicon-carbon composite materials mainly include chemical vapor deposition, mechanical alloying and solution method. Among them, vapor-deposited silicon-carbon negative electrode materials have significant cost reduction space and relatively mature industrial mass production conditions in the future, so they have become the hottest negative electrode material track in the current new energy field. The chemical vapor deposition method uses gas-phase chemical reactions to form a thin film on the surface of the substrate. In the production of silicon-carbon negative electrode materials, the chemical vapor deposition method uses high temperature to decompose silicon source gases such as silane, and by precisely controlling the reaction parameters, a uniform, high-purity silicon-carbon composite material is deposited on the surface of the carbon-based material. However, the requirements for equipment and reaction conditions are high, resulting in high production costs.

[0005] As a typical representative, the silicon-carbon negative electrode material SCC55 produced by Group 14 in the United States creatively uses vapor deposition technology, takes nanocarbon skeleton as the main structure, and stores nanosilicon negative electrode inside the carbon skeleton to stabilize the volume expansion of silicon particles during charging and discharging. However, this route faces problems such as the inability to achieve continuous production, poor consistency of different batches of products, and high cost, and has not yet achieved real mass production. When studying silicon-carbon materials, Professor Cui Yi's research team at Stanford University first prepared a carbon skeleton negative electrode loaded with high-capacity crystalline silicon through a two-step chemical vapor deposition method, and then coated a layer of highly elastic polymer on the surface of the skeleton through a polymerization reaction to greatly improve the mechanical strain performance of the electrode. In addition, Professor Cui Yi's team also designed some innovative structures to improve the performance of the material, such as yolk-shell structure and micro-pomegranate configuration. However, the preparation cost of these advanced structures is relatively high, and the preparation process is relatively complicated and the safety factor is low, which to a certain extent limits the application of silicon-carbon materials. It is worth pointing out that both Group 14 and Cui Yi's Amprius face safety issues in the use of silane. The large-scale safe use of this highly toxic and explosive gas is a key problem faced in the industrial production of silicon-carbon negative electrodes.

[0006] In summary, the present invention will adopt a solid silicon source, overcome the key problems in traditional technology through innovative structural design and process improvement, explore a highly efficient, stable and widely applicable method for preparing silicon-based negative electrode materials, completely avoid the use of silane gas, and is expected to show great prospects in the application of high energy density battery technology. Summary of the invention

[0007] The purpose of the present invention is to develop an ultrafine nano silicon-based negative electrode material and a preparation method thereof based on in-situ high-temperature phase change in a confined microcavity, aiming to solve the problems of low utilization rate, low electron transfer, and significant volume change during the preparation process of silicon as a negative electrode material for lithium-ion batteries.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A method for preparing ultrafine nano silicon-based negative electrode materials based on in-situ high-temperature phase change in a specific confined microcavity comprises the following steps:

[0010] (1) uniformly mixing silicon and a conductive porous material in a solvent and preliminarily reducing the size to obtain a mixed slurry;

[0011] (2) reforming and granulating the mixed slurry obtained in step (1) to form solid particles, which provide a basis for the subsequent construction of the coating layer;

[0012] (3) coating the particles obtained by the reforming and granulation in step (2), selecting a coating shell layer with high mechanical strength, high toughness and high stability to form a coating layer with a confined microcavity structure, wherein the confined microcavity is tightly coated on the surface of the shell layer, which refers to a closed or semi-closed space constructed on the surface of the particles obtained by the reforming and granulation by the coating layer, which is used to limit the diffusion range of silicon after gasification and achieve efficient utilization;

[0013] (4) The product obtained in step (3) is loaded into a rapid high-temperature reaction zone, and the temperature is rapidly increased by a precisely controlled heating device, so that the silicon source reaches the sublimation temperature in a very short time and is evenly distributed in the confined microcavity. After the sublimation process is completed, the rapid cooling system is immediately started, and the temperature in the reaction zone is rapidly reduced in an instant through the rapid circulation of the cooling medium. The silicon vapor is rapidly condensed in this process to form ultrafine nanoparticles below 10 nm, which are effectively embedded in the interior of the porous conductive material.

[0014] The silicon described in step (1) is nano-silicon or micro-silicon with a particle size of 0.05-10 μm. The nano-silicon or micro-silicon is a powder, suspension or solution of inorganic silicon or organic silicon, the inorganic silicon includes silicate, quartz, sodium silicate and silicon carbide, and the organic silicon includes methylsilane, vinylsilane, aminosilane and epoxysilane.

[0015] The silicon described in step (1) is preferably nano-silicon with an average particle size of 50 nm. The smaller the size of nano-silicon, the easier it is to gasify. In addition, based on existing industrial means, 50 nm nano-silicon can be obtained in batches and has a wide source. The nano-scale size enables the silicon material to better adapt to volume changes during the charging and discharging process, thereby improving the energy density and first charge efficiency of lithium-ion batteries. In addition, nano-silicon materials have the excellent performance of long-cycle fast charging, which improves the convenience of battery use.

[0016] Optionally, the conductive porous material is one or more of a porous carbon material, a porous metal material, a porous conductive polymer, a porous graphene, a porous oxide, a metal organic framework, an aerogel, a covalent organic framework or a carbon-coated porous material, preferably a porous carbon material. The voids inside the porous carbon material can absorb the volume expansion of silicon. In addition, the effective coating of silicon by the porous carbon material can greatly reduce the contact between silicon and the electrolyte and prevent the repeated growth of the SEI film, thereby greatly improving the initial coulombic efficiency of the lithium battery.

[0017] Preferably, the porous carbon material is at least one of micro-mesoporous carbon, activated carbon, carbon aerogel, carbon nanotube, graphene aerogel, ordered mesoporous carbon, activated carbon fiber, porous carbon ball, carbonized polymer porous carbon, preferably activated carbon. Activated carbon has a well-developed internal pore structure, a large specific surface area, a strong adsorption capacity, good chemical stability, and can be used in high temperature and strong oxidant environments. The unique microporous structure of activated carbon makes it have excellent adsorption capacity, and is particularly suitable for adsorbing particles with smaller molecular diameters. In addition, the interaction force between the molecules of activated carbon (van der Waals attraction) also promotes its adsorption capacity, so that more molecules are attracted and stay in the pores of activated carbon.

[0018] Preferably, the porous metal material is at least one of foam aluminum, foam nickel, foam copper, porous titanium, porous gold, porous magnesium, porous iron, porous cobalt, porous tungsten, porous molybdenum or porous alloy; the porous conductive polymer is at least one of polypyrrole, polyaniline, polythiophene and its derivatives, polythiophene-conductive polymer composites or conductive polymer-carbon material composites; the porous graphene is at least one of three-dimensional graphene aerogel, porous reduced oxide graphene or porous graphene foam; the porous oxide conductive material is at least one of porous titanium dioxide, porous tin oxide, porous silicon dioxide, porous iron oxide, porous magnesium oxide, porous zinc oxide or porous lithium titanate; the metal organic framework is ZIF series, MIL series, NU series, HKUST-1, IRMOF series, UiO series, MOF-5 or at least one of the PCN series; the covalent organic framework is at least one of COF-1, COF-5, COF-102, COF-108, TP-COFs, LZU-COF, NUS-COFs, PI-COFs or TF-COFs; the aerogel is at least one of carbon-based, silicon-based, sulfur-based, metal oxide-based, metal-based, single-component, multi-component, inorganic, organic or inorganic-organic aerogel; the carbon-coated porous material is at least one of carbon-coated porous carbon, carbon-coated porous carbon, carbon-coated porous metal, carbon-coated porous conductive polymer, carbon-coated porous graphene, carbon-coated porous oxide, carbon-coated metal organic framework, carbon-coated covalent organic framework, carbon-coated porous polymer, carbon-coated porous glass, carbon-coated ceramics, carbon-coated zeolite or porous carbon-coated bio-based porous material.

[0019] Optionally, the solvent in step (1) is one or more of ethanol, deionized water, isopropanol, propylene glycol methyl ether, N,N-dimethylformamide, N-methylpyrrolidone, ethyl acetate, cyclohexanone, and dichloromethane.

[0020] Optionally, in step (1), the mass ratio of silicon, conductive porous material and solvent is 1:0.1-100:1-100.

[0021] Optionally, the uniform mixing method described in step (1) is one of sand milling, ball milling or air milling. The rotation speed of the sand mill is 1-5000r / s, the sand milling time is 1-60h, the sand milling temperature is 15-100°C, and the sand milling pressure is 0.1-100MPa; the classifier frequency of the air mill is 0-103Hz, the fan frequency is 0-50Hz, and the feeding frequency is 0-50Hz; the ball mill cylinder rotation speed is 0-38r / min, and the ball loading is 0-330t. Sand milling is preferred. The sand mill uses high-speed rotating grinding discs and grinding beads for grinding, which can quickly grind the material into the required particle size. It has the advantages of efficient grinding, high fineness, low cost, and continuous operation. Technological advances in sand mills have made them superior to ball mills in terms of grinding efficiency and product particle size distribution. In addition, Lin Wenzhong pointed out in his research that compared with other grinding equipment, such as air flow mills, sand mills have the advantages of low energy consumption, high fineness, strong continuity and high efficiency.

[0022] Optionally, the reforming granulation method described in step (2) is one of spray drying granulation, compression granulation, fluidized bed granulation, wet granulation, drum granulation, sol-gel granulation, electrochemical deposition granulation or solution impregnation granulation. Spray drying granulation technology is preferred, which can process a large amount of materials in a short time, has fast drying ability, and achieves high-yield and high-efficiency production. Spray drying granulation sprays liquid or solution-like materials through a high-pressure nozzle, quickly dries into tiny particles, is convenient for subsequent coating, is easy to operate, and has strong stability. In addition, spray drying granulation technology has become a preferred technology due to its wide applicability, controllability of product quality, flexibility of operation, and continuous automated operation. Preferably, the gas temperature range is 80-250°C, the air flow pressure is 0.01-5MPa, and the injection speed is 1-20rmp during the spray drying granulation process.

[0023] Optionally, the particle size range of the microparticles in step (2) is 1-100 μm, preferably 1-20 μm. The cycle performance of silicon-based negative electrode materials is closely related to the granulation size. Smaller particle size can provide more contact area, which is conducive to the embedding and extraction of lithium ions, thereby improving the cycle performance of the battery. However, smaller particle size will also increase the specific surface area in contact with the electrolyte, resulting in an increase in the charge consumed by the formation of the SEI film during the initial charge and discharge process, thereby causing an increase in irreversible capacity loss. Therefore, a reasonable particle size distribution is crucial to improving the initial capacity and efficiency of the battery.

[0024] Optionally, the coating layer described in step (3) is one of a carbon coating layer, a metal coating layer, an oxide coating layer, a nitride coating layer or a polymer coating layer.

[0025] The carbon coating layer is one of graphene, carbon nanotubes, amorphous carbon, and graphite coating; the metal coating layer includes one of silver, tin, cobalt, aluminum, nickel, copper, zinc, titanium, gold, magnesium, iron, tungsten, molybdenum, and alloys; the oxide coating layer includes one of aluminum oxide, titanium oxide, zirconium oxide, silicon oxide, manganese oxide, magnesium oxide, nickel oxide, and cerium oxide; the nitride coating layer includes titanium nitride, silicon nitride, aluminum nitride, boron nitride, and zirconium nitride; the polymer coating layer includes one or more of dopamine, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, polyvinylidene fluoride, polyethyleneimine, polythiophene, polypyrrole, polyaniline, polyacrylonitrile, and polyethylene glycol.

[0026] Carbon coating is a common modification method. By covering the silicon surface with a layer of carbon, the conductivity of silicon-based negative electrode materials can be effectively improved, because carbon has good conductivity and can achieve rapid transmission of lithium ions. In addition, the carbon coating layer also has good toughness, can adapt to the stress changes caused by volume expansion, and has a certain ductility, thereby protecting the structural stability of silicon-based materials during the charging and discharging process.

[0027] Metal and metal oxide coatings use the excellent mechanical properties of metals and their alloys, such as high elastic modulus, high hardness, and good electrical conductivity, to alleviate the expansion effect of nano-silicon during the cycle and improve the electrical conductivity of nano-silicon. The metal coating can provide mechanical stress for silicon expansion, but at the same time, the metal must have good electrical conductivity, be able to transfer lithium ions to the silicon in the center, and not react chemically with lithium ions and battery electrolyte. Compared with carbon coatings, metal and metal oxide coatings place higher requirements on the selection of coating metals.

[0028] Polymer coating can form a layer of high molecular weight polymer on the silicon surface, which can also limit the volume change of silicon during the charging and discharging process to a certain extent, slow down the rupture of the SEI film, and thus improve the conductivity of silicon to a certain extent, but it is not as common as carbon coating and metal coating.

[0029] Optionally, the coating method in step (3) is one or more of microemulsion coating, chemical plating, hydrothermal method, spray pyrolysis, electroplating, chemical vapor deposition, physical vapor deposition, electrochemical deposition, pyrolysis, and solution-gel method.

[0030] Optionally, the coating layer in step (3) has a thickness of 1-1000 nm, the stirring time is 1-8 h, and the mass ratio of the coating layer to the particles is 1:0.2-1:20. A coating layer with a certain thickness on the surface has a significant effect on the cycle stability of the silicon-based negative electrode material, can effectively inhibit the decomposition of the electrolyte on the surface of the silicon negative electrode, and stabilize the SEI film structure on the surface of the silicon negative electrode, thereby significantly improving the cycle performance of the silicon-based negative electrode material. Preferably, the coating layer has a thickness of 30 nm and a stirring time of 4 h.

[0031] Optionally, when the coating method in step (3) is polymer carbon coating, carbonization treatment is required: heating to a carbonization temperature of 500-900°C and keeping warm in an inert atmosphere, then naturally cooling to room temperature, the heating rate is 1-20°C / min, and the holding time is 0.1-72h. The specific operation of the carbonization treatment is to dry the product and place it in a tubular furnace, heating to the carbonization temperature and keeping warm in an inert atmosphere, and after completion, wait for the tubular furnace to naturally cool to room temperature.

[0032] Optionally, the transient heating method in step (4) is one of Joule heating, microwave heating, electric spark heating, plasma heating, infrared heating, combustion heating, thermal explosion heating, thin film electric heater heating and electromagnetic pulse heating.

[0033] Optionally, in step (4), the temperature is raised to 800-1000°C by at least one pulse, and the heating rate is 1×10 6 -100℃ / s, after reaching the target temperature, the system enters the insulation stage, the insulation time is 0.01-200s, after the insulation stage, the cooling operation is immediately carried out to form ultrafine nanoparticles. The single pulse time is 0.01s-100s, which refers to the total time from the start of heating to the end of cooling, including heating, insulation and cooling processes. Each pulse operation includes a complete heating-insulation-cooling cycle, the number of pulses is unlimited, and the pulse interval is 0.1s-100s, which refers to the time interval between the end of one pulse and the start of the next pulse. During the heating stage, the temperature in the device rises rapidly from the starting temperature to the set target temperature, which is determined according to the experimental requirements. After reaching the target temperature, the system enters the insulation stage, and the temperature remains constant to ensure that the silicon source is fully sublimated and diffused. The insulation time can be flexibly adjusted according to the material properties and process requirements to achieve the best effect. After the insulation is over, the system immediately starts to cool down, and the temperature is quickly reduced to a safe level through rapid cooling, which prompts the silicon vapor to condense quickly and form ultrafine nanoparticles. In the process of preparing battery materials, the heating and cooling rates have a significant effect on crystal nucleation and particle size. Faster heating and cooling rates will cause drastic changes in system temperature, accelerate crystal nucleation, and the crystal particles formed are smaller due to the short growth time. Such small-particle crystals are conducive to the optimization of the microstructure of the material, making the silicon particles more evenly distributed, thereby improving the uniformity and stability of the material, and further enhancing the performance stability of the battery in multiple charge and discharge cycles. The silicon-based negative electrode material prepared by the rapid heating technology has excellent mechanical stability and long cycle life. By controlling the heating rate, the performance of the silicon-based negative electrode material can be positively affected.

[0034] Optionally, the cooling rate in step (4) is 1×10 6 -100℃ / s, until room temperature.

[0035] Optionally, the atmosphere in the heating zone in step (4) is a non-oxidizing atmosphere, including a mixture of one or more gases selected from the group consisting of low vacuum, helium, argon, and nitrogen.

[0036] The principle of the present invention is based on in-situ high-temperature phase change in a confined microcavity to prepare ultrafine nano-silicon-based negative electrode materials, which mainly involves the following key technical steps and mechanisms:

[0037] 1. Construction of specific confined microcavity structure:

[0038] By constructing a coating layer on the surface of a porous conductive material, a closed or semi-closed microcavity structure is formed. The microcavity structure is used to limit the vaporization diffusion range and distribution path of silicon during the high-temperature phase change process, so as to improve the utilization efficiency and distribution uniformity of silicon.

[0039] 2. In-situ high temperature phase change:

[0040] Transient high-temperature technology (such as Joule heat, microwave heating, etc.) is used to rapidly sublimate silicon in a confined microcavity and instantly condense into ultrafine nanoparticles below 10nm. By controlling the temperature and the speed of heating and cooling, precise size control and uniform distribution of silicon can be achieved.

[0041] 3. Use of conductive porous materials:

[0042] Materials with high conductivity and porous structure (such as porous carbon materials, metal organic frameworks, etc.) are selected as the matrix. These porous materials have the function of adsorbing vaporized silicon on the one hand, and on the other hand, they can provide a good electron conduction path and physically buffer the volume expansion of silicon during the charging and discharging process to avoid material pulverization.

[0043] 4. The role of the coating layer:

[0044] The coating layer (such as carbon layer and oxide layer) constructed on the surface of the material not only forms a confined microcavity, but also chemically interacts with silicon to enhance the mechanical and chemical stability of the material and inhibit structural fracture caused by volume changes of silicon.

[0045] The present invention improves the utilization efficiency and conductivity of the material by nano-sizing silicon and distributing it evenly in a porous structure, solving the problems of volume expansion and poor conductivity of silicon in battery applications. The construction of confined microcavities and transient high-temperature phase change technology together achieve precise control of the material structure, thereby improving the cycle stability and electrochemical performance of the electrode material. This innovative method provides new possibilities for the application of silicon-based negative electrode materials in lithium-ion batteries.

[0046] The method for preparing ultrafine nano-silicon-based negative electrode materials based on in-situ high-temperature phase change in a specific confined microcavity proposed in the present invention has the following advantages and outstanding effects compared with the prior art:

[0047] First, through the combination of confined microcavity and high-temperature phase change technology, the structural stability and cycle life of the material are greatly enhanced, and the cycle stability and reversible capacity of the battery are significantly improved. The uniform distribution and high conductivity of the material in the conductive porous structure significantly improve the electrochemical performance of the battery, showing higher energy density and charge and discharge efficiency.

[0048] Secondly, the invention simplifies the material preparation process, using efficient material use and precise size control to reduce production costs and process complexity. This innovative method is suitable for lithium-ion batteries and broadens the application range of silicon-based negative electrode materials.

[0049] In addition, using transient heating technology, silicon rapidly changes phase in the coating shell under thermodynamically driven non-steady-state conditions. The coating layer confines the vaporized silicon, while the conductive porous material can quickly adsorb the vaporized silicon. The nanoparticles formed after transient cooling, combined with the good mechanical properties of the conductive porous material, effectively limit the volume expansion of silicon, enhance the conductivity, inhibit the structural rupture caused by the huge volume change of silicon, avoid the loss of active sites, form a stable SEI, further improve the cycle stability, and increase the conductivity of the electrode.

[0050] It is extremely important that the present invention is completely different from the silane gas-based chemical vapor deposition technology used by Group 14 and Amprius, avoiding the highly toxic and explosive silane, and will greatly promote the large-scale innovative preparation of silicon-carbon composite materials.

[0051] In summary, the present invention will adopt a solid silicon source, overcome the key problems in traditional technology through innovative structural design and process improvement, explore a highly efficient, stable and widely applicable method for preparing silicon-based negative electrode materials, completely avoid the use of silane gas, and is expected to show great prospects in the application of high energy density battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a basic principle diagram of the preparation method of the present invention.

[0053] Figure 2 This is a scanning electron microscope (SEM) image of the spherical silicon-carbon hybrid material obtained in Example 1 of the present invention.

[0054] Figure 3 This is a scanning electron microscope (SEM) image of the spherical silicon-carbon hybrid material particles after carbon coating in Example 1 of the present invention.

[0055] Figure 4 This is a cross-sectional SEM image of Example 1 of the present invention before the Joule heat pulse, showing the material's uniformly distributed and dense internal structure of silicon and carbon before the Joule heat pulse.

[0056] Figure 5 This is a cross-sectional SEM image of Example 1 of the present invention after the Joule heat pulse, which shows the changes in the internal structure of the material after the Joule heat pulse. The silicon is vaporized into nanoparticles and enters the porous carbon.

[0057] Figure 6 The figure shows the comparison of the rate performance of button cells assembled before and after Joule heat pulse treatment in Example 1 of the present invention.

[0058] Figure 7 The figure shows a comparison of the first discharge efficiency of button cells assembled before and after Joule heat pulse treatment in Example 1 of the present invention.

[0059] Figure 8 The present invention presents a comparison of the cycle performance of button cells assembled before and after Joule heat pulse treatment in Example 1 of the present invention, showing the capacity change of the battery at different cycle times, and the cycle stability of the sample treated with Joule heat is improved.

[0060] Fig. 9 This is a graph showing the capacity change of the battery of Example 2 after 500 cycles.

[0061] Fig.10 This is a diagram of the battery cycle performance in Example 3.

[0062] Fig.11 This is the morphology of the silicon carbon sphere in Example 4.

[0063] Fig.12 This is a scanning electron microscope (SEM) image of the silicon-carbon mixed particles in Example 5.

[0064] Fig.13 This is a scanning electron microscope (SEM) image of the silicon-carbon mixed particles in Example 6 whose shells were broken by gas.

[0065] Fig.14 This is a cross-sectional morphology diagram of the silicon particles in Example 7 when they are not completely vaporized. DETAILED DESCRIPTION

[0066] The following content appropriately refers to the accompanying drawings to describe in detail and specifically disclose the invention of the present application, which provides a method for preparing ultrafine nano silicon-based negative electrode materials based on in-situ high-temperature phase change in a confined microcavity. Certain unnecessary details may be omitted in the description, such as well-known matters and repeated descriptions of the same structure. This is done to avoid the description becoming lengthy so that those skilled in the art can better understand it. In addition, the drawings and the following description are intended to help those skilled in the art fully understand the present application, rather than to limit the subject matter recorded in the claims. Obviously, the described embodiments are only part of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should also fall within the scope of protection of the present invention.

[0067] If not otherwise specified, all technical features and optional technical features in this application can be combined with each other to form a new technical solution. In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0068] Embodiment 1:

[0069] Mixed preparation: Weigh 50g of nano-silicon with an average particle size of 50nm and 50g of activated carbon, disperse them in 900g of ethanol, pour them into a sand mill, control the temperature to 25°C, and sand mill at 360r / s for 7h to obtain a silicon-carbon mixed slurry. Through this step, the size of the silicon-carbon material is initially reduced and highly evenly mixed. The density of the inside of the spray-dried sphere is controlled by controlling the silicon-carbon ratio and concentration. The loose interior may easily lead to the coating entering the interior during subsequent coating; too much nano-silicon and insufficient porosity of activated carbon may easily lead to condensation and agglomeration of nano-silicon on the surface. Oxidation can be prevented by controlling the temperature, and the uniformity of the silicon-carbon mixture can be adjusted by controlling the sand milling speed and time.

[0070] Spray drying: spray drying the mixed slurry, controlling the gas temperature to 150°C, the gas pressure to 0.2Mpa, and the injection speed to 15rmp. In this step, the size of the manufactured spheres is controlled by controlling the gas pressure and injection speed. If the size is too large, the coating layer will not be completely coated. If the size is too small, the coating layer thickness will be difficult to control. The scanning electron microscope (SEM) image of the obtained spherical silicon-carbon mixed material is as follows: Figure 1 As shown, it can be seen that the figure shows spherical particles without significant aggregation or agglomeration.

[0071] Figure 2:Scanning electron microscope (SEM) images of spherical silicon-carbon hybrid materials obtained after spray drying are shown. As can be seen in the figure, the material presents uniform spherical particles, with large particles ranging in diameter from a few microns to more than ten microns, and small particles within a few microns in diameter. The distribution of particles is relatively uniform, and there is no significant aggregation or agglomeration.

[0072] Carbon coating treatment: The above-obtained powder was subjected to carbon coating treatment. 1 g of dopamine and 1 g of F127 (polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer) were added to a mixed solution of 50 ml of ethanol and deionized water (volume ratio 1:1), stirred evenly, 1 g of the spray-dried powder was added, stirred for 15 min, and then 1.5 mL of ammonia water was added and stirred for 1 h.

[0073] Figure 3 :Scanning electron microscope (SEM) images of spherical silicon-carbon hybrid material particles after carbon coating are shown. As can be seen from the figure, the carbon coating process attaches a large number of spherical particles to the surface of the material, and the distribution of the particles is relatively uniform.

[0074] Joule heat treatment: Take 0.1g of material and place it in a 8cm long carbon felt. Place the carbon felt between the positive and negative electrodes of the Joule heat. The device is in a high vacuum state. The atmosphere is controlled to ensure that it is not oxidized during the instantaneous heating process. Start the Joule heat device power supply in a high vacuum atmosphere, adjust the current and voltage, and instantly raise the temperature to 940℃. Pulse for 30s multiple times to reach the sublimation point of nano-silicon, so that the nano-silicon is evenly diffused in the microcavity after vaporization. If the temperature is too high, the internal pressure is high, and it is easy to break through the coating layer and generate silicon carbide. If the temperature is too low, the nano-silicon is not completely vaporized. The pulse makes the nano-silicon evenly distributed, refined to an ultra-fine nano size below 10nm, and does not agglomerate. If the time is too long, the coating layer is easy to break. If the time is too short, the vaporization is incomplete. The best experimental effect is achieved by adjusting the time and temperature.

[0075] Figure 4 :Scanning electron microscope (SEM) images of carbon-coated spherical silicon-carbon hybrid material particles before Joule heat treatment are shown. The image shows that the structure of the particles is very dense, with some irregular structural features, and the internal structure is relatively uniform.

[0076] Figure 5 :Scanning electron microscope (SEM) images of spherical silicon-carbon hybrid material particles after Joule heat treatment are shown. After treatment, new pore structures are formed inside and on the surface of the material. These pores are caused by the gasification and nano-scaling of silicon. It can be observed from the SEM images that the material structure becomes more complex and the internal pores increase.

[0077] The silicon-carbon composite material prepared in Example 1 was assembled into button cells before and after Joule heating, and the electrochemical performance was tested. In the production of button cells, a metal lithium sheet was selected as the counter electrode, and the preparation method of the silicon-carbon pole piece was as follows: the silicon-carbon composite material, the conductive agent SP, and the binder PVDF were uniformly mixed in a mass ratio of 7:1.5:1.5, coated on a copper foil, and vacuum dried at 80°C for 12 hours. The dried pole piece was roll-pressed, cut into discs with a diameter of 11 mm, weighed, and placed in a vacuum glove box for button cell assembly.

[0078] Figure 6 The relationship between the specific capacity and the number of cycles of the silicon-carbon composite material prepared by Example 1 of the present invention before and after Joule heat treatment at different charge and discharge rates (C-rate) is shown.

[0079] The horizontal axis (Cycle Number) indicates the number of cycles of the battery, ranging from 0 to 40 cycles.

[0080] Vertical axis (Capacity, mAh / g): represents the specific capacity of the battery, in mAh / g, ranging from 0 to 2500mAh / g.

[0081] The curves are labeled:

[0082] Black solid dot curve: represents the battery performance after Joule heating treatment.

[0083] Gray solid square curve: represents the battery performance without Joule heat treatment.

[0084] The "0.1C", "0.2C", "0.5C", "1C", "2C", and "5C" marked in the figure represent different charge and discharge rates. Usually, C-rate indicates how many times the rated capacity the battery is charged and discharged. For example, 1C means that the charge and discharge are completed within 1 hour. It can be seen that as the C-rate increases, the specific capacity decreases. This is due to the increase in battery polarization and overpotential at high rates. However, the specific capacity of the battery treated with Joule heat at each rate is significantly higher than that of the untreated battery.

[0085] Rate cycling stability: After being tested at different rates, the specific capacity of the battery can still be restored to a high level when it is restored to a low rate (such as 0.1C), especially the battery after Joule heat treatment, which shows good rate cycling stability.

[0086] Figure 7 The relationship curve between voltage and specific capacity of the silicon-carbon composite material prepared by Example 1 of the present invention before and after Joule heat treatment during the first charge and discharge process is shown. In the figure:

[0087] Horizontal axis (Specific Capacity, mAh / g): represents the specific capacity of the battery, in mAh / g, ranging from 0 to 2500mAh / g.

[0088] Vertical axis (Voltage, V vs. Li / Li+): represents the voltage of the battery relative to the voltage of lithium / lithium ions, ranging from 0V to 3V.

[0089] The two curves are:

[0090] Gray solid line: represents the voltage-capacity curve of the battery after Joule heat treatment during the first charge and discharge process.

[0091] Black solid line: represents the voltage-capacity curve of the battery during the first charge and discharge process before Joule heat treatment.

[0092] Voltage platform and specific capacity:

[0093] Before Joule heat treatment (black line): The battery has unclear voltage platforms at around 0.2V and 0.7V. The charge capacity before treatment is low, at about 1250mAh / g.

[0094] After Joule heat treatment (gray line): After Joule heat treatment, the battery's charge and discharge platform is more obvious, and the charge specific capacity is increased to nearly 1500mAh / g. This shows that heat treatment reduces the silicon particle size and improves the utilization rate, thereby enhancing the lithium storage capacity and electrochemical activity.

[0095] After Joule heat treatment, the voltage change of the battery during the charge and discharge process is smoother, indicating that the electrochemical reaction of the material is more stable. After heat treatment, the initial specific capacity of the battery increased significantly, showing the positive effect of heat treatment on improving material performance.

[0096] Figure 8 The cycle performance of button-type batteries assembled with the silicon-carbon composite material prepared in Example 1 of the present invention before and after Joule heat treatment is shown.

[0097] The horizontal axis (Cycle Number) indicates the number of cycles of the battery, from 0 to 300 cycles.

[0098] The left vertical axis (Specific Capacity, mAh / g) represents the specific capacity of the battery, in mAh / g, ranging from 0 to 2500mAh / g.

[0099] In the figure, the black solid circles represent the Coulombic efficiency after Joule heating treatment, and the gray solid circles represent the Coulombic efficiency before Joule heating treatment.

[0100] The two curves are labeled:

[0101] The black solid dot curve represents the battery performance after Joule heat treatment, showing a significant improvement in the battery specific capacity after heat treatment.

[0102] Gray solid dot curve: represents the battery performance before Joule heat treatment, and its specific capacity is significantly lower than the result after heat treatment.

[0103] It can be seen that the initial specific capacity of the battery is not much different before and after Joule heat treatment, but after multiple cycles, the battery after Joule heat treatment shows a higher capacity retention rate, indicating that the heat treatment process significantly improves the cycle stability of the battery.

[0104] The battery was tested at a current density of 1 A / g.

[0105] Embodiment 2:

[0106] This embodiment is basically the same as the embodiment 1, except that 25 g of nano-silicon and 50 g of porous carbon are weighed and dispersed in 675 g of ethanol and poured into a sand mill. The capacity can be adjusted by changing the ratio of silicon to carbon.

[0107] Fig. 9 The capacity change of a battery with a silicon-carbon ratio of 1:2 after 500 cycles is demonstrated.

[0108] Embodiment 3:

[0109] This embodiment is basically the same as the embodiment 1, except that graphene is used instead of porous carbon. The high electrical conductivity of graphene can improve the electron transfer efficiency and effectively improve the cycle stability.

[0110] Fig.10 The battery cycling performance after graphene replaced porous carbon was demonstrated. The high conductivity of graphene can improve the electron transfer efficiency to effectively improve the cycle stability.

[0111] Embodiment 4:

[0112] This embodiment is basically the same as the embodiment 1, except that the mixed slurry is granulated by a fluidized bed. The fluidized bed can also aggregate silicon and carbon into spherical composites.

[0113] Fig.11 Silicon carbon spheres after granulation using a fluidized bed are shown.

[0114] Embodiment 5:

[0115] This embodiment is basically the same as the embodiment 1, except that the carbon coating layer is manufactured by physical vapor deposition. Physical vapor deposition can achieve precise film thickness control and uniform deposition, and the deposited carbon film is pure and has a low impurity content, which helps to improve the electrochemical properties.

[0116] Fig.12 Scanning electron microscope (SEM) images of silicon-carbon hybrid particles coated by physical vapor deposition are shown. The carbon layer has a smooth surface and there are no small carbon spheres produced by dopamine self-polymerization.

[0117] Embodiment 6:

[0118] This embodiment is basically the same as embodiment 1, except that dopamine is used to coat the silicon-carbon mixed particles, and the coating thickness is controlled to be 500 nm. With an increased coating thickness, the particles can withstand greater internal pressure, are less likely to break, and can have a higher transient temperature rise, and the internal phosphorus content can be increased.

[0119] Fig.13 The scanning electron microscope (SEM) image shows that the gas breaks through the shell due to insufficient shell thickness and excessive internal pressure. Therefore, when designing the material, the appropriate coating thickness must be selected based on the specific material properties and internal phosphorus content to effectively confine the internal silicon vapor and maintain the integrity of the shell.

[0120] Embodiment 7:

[0121] This embodiment is basically the same as embodiment 1, except that the Joule heat device power supply is started in an atmosphere filled with argon, the temperature rises to 1000°C instantly, and multiple pulses of 5s are applied. Different temperature and time conditions can regulate the degree of gasification of silicon particles.

[0122] Fig.14 The cross-sectional morphology of silicon particles is shown when they are not completely vaporized.

[0123] In summary, the present invention provides a method for preparing ultrafine nano silicon-based negative electrode materials based on in-situ high-temperature phase change in a confined microcavity. The transient temperature rise causes silicon to vaporize rapidly and be adsorbed by the porous conductive material. The microcavity structure limits the vaporized silicon to fill the material inside the cavity. After instant condensation, nanoparticles are formed and confined in the pores, which enhances conductivity, provides a buffer for the expansion of silicon, effectively inhibits the structural rupture of silicon caused by volume change, avoids the loss of active sites, and thus improves cycle stability.

[0124] The above is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any equivalent replacement or change made by any technician familiar with the technical field within the technical scope disclosed by the present invention and based on the technical solution and its conception of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing ultrafine nano-silicon-based negative electrode materials based on in-situ high-temperature phase change in a specific confined microcavity, characterized in that: The following steps are involved: (1) uniformly mixing silicon and a conductive porous material in a solvent and reducing their particle sizes to obtain a mixed slurry; (2) reforming and granulating the mixed slurry to form solid particles; (3) coating the obtained particles to form a coating layer with a confined microcavity structure to limit the diffusion range of silicon after vaporization; (4) The coated product is loaded into the reaction zone, and the temperature is rapidly raised to the sublimation temperature of the silicon source so that it is evenly distributed in the confined microcavity, and rapidly cooled so that the silicon vapor is quickly condensed into ultrafine nanoparticles with a particle size of less than 10 nm, which are embedded in the porous conductive material.

2. The method according to claim 1, characterized in that The silicon described in step (1) is nano silicon or micro silicon with a particle size of 0.05-10 μm.

3. The method according to claim 2, characterized in that The nano-silicon or micro-silicon is powder, suspension or solution of inorganic silicon or organic silicon. The inorganic silicon includes silicate, quartz, sodium silicate and silicon carbide. The organic silicon includes methylsilane, vinylsilane, aminosilane and epoxysilane.

4. The method according to claim 1, characterized in that: The conductive porous material described in step (1) is one or more of porous carbon materials, porous metal materials, porous conductive polymers, porous graphene, porous oxides, metal organic frameworks, aerogels, covalent organic frameworks or carbon-coated porous materials.

5. The method according to claim 4, characterized in that The porous carbon material is at least one of micro-mesoporous carbon, activated carbon, carbon aerogel, carbon nanotubes, graphene aerogel, ordered mesoporous carbon, activated carbon fiber, porous carbon ball or carbonized polymer porous carbon.

6. The method according to claim 4, characterized in that: The porous metal material is at least one of foam aluminum, foam nickel, foam copper, porous titanium, porous gold, porous magnesium, porous iron, porous cobalt, porous tungsten, porous molybdenum or porous alloy; the porous conductive polymer is at least one of polypyrrole, polyaniline, polythiophene and its derivatives, polythiophene-conductive polymer composite materials or conductive polymer-carbon material composite materials; the porous graphene is at least one of three-dimensional graphene aerogel, porous reduced oxide graphene or porous graphene foam; the porous oxide conductive material is at least one of porous titanium dioxide, porous tin oxide, porous silicon dioxide, porous iron oxide, porous magnesium oxide, porous zinc oxide or porous lithium titanate; the metal organic framework is ZIF series, MIL series, NU series, HKUST-1, IRMOF series, UiO series, MOF-5 or P CN series; the covalent organic framework is at least one of COF-1, COF-5, COF-102, COF-108, TP-COFs, LZU-COF, NUS-COFs, PI-COFs or TF-COFs; the aerogel is at least one of carbon-based, silicon-based, sulfur-based, metal oxide-based, metal-based, single-component, multi-component, inorganic, organic or inorganic-organic aerogel; the carbon-coated porous material is at least one of carbon-coated porous carbon, carbon-coated porous carbon, carbon-coated porous metal, carbon-coated porous conductive polymer, carbon-coated porous graphene, carbon-coated porous oxide, carbon-coated metal organic framework, carbon-coated covalent organic framework, carbon-coated porous polymer, carbon-coated porous glass, carbon-coated ceramics, carbon-coated zeolite or porous carbon-coated bio-based porous material.

7. The method according to claim 1, characterized in that The solvent in step (1) is one or more of ethanol, deionized water, isopropanol, propylene glycol methyl ether, N,N-dimethylformamide, N-methylpyrrolidone, ethyl acetate, cyclohexanone and dichloromethane.

8. The method according to claim 1, characterized in that In step (1), the mass ratio of silicon, conductive porous material and solvent is 1:0.1-100:

1.

9. The method according to claim 1, characterized in that: The uniform mixing method described in step (1) is one of sand milling, ball milling or air flow milling.

10. The method according to claim 1, characterized in that The reforming granulation method described in step (2) is one of spray drying granulation, compression granulation, fluidized bed granulation, wet granulation, drum granulation, sol-gel granulation, electrochemical deposition granulation or solution impregnation granulation.

11. The method according to claim 10, characterized in that The reforming granulation method described in step (2) is spray drying granulation, and the gas temperature during spray drying is 80-250° C., the gas flow pressure is 0.01-5 MPa, and the injection speed is 1-20 rpm.

12. The method according to claim 1, characterized in that The particle size of the microparticles in step (2) ranges from 1 to 100 μm.

13. The method according to claim 1, characterized in that The coating layer described in step (3) is one of a carbon coating layer, a metal coating layer, an oxide coating layer, a nitride coating layer and a polymer coating layer.

14. The method according to claim 1, characterized in that The coating treatment method in step (3) is one or more of microemulsion coating method, chemical plating method, hydrothermal method, spray pyrolysis method, electroplating method, chemical vapor deposition, physical vapor deposition, electrochemical deposition, pyrolysis method, and solution-gel method.

15. The method according to claim 1, characterized in that In step (3), the thickness of the coating layer is 1-1000 nm, the stirring time is 1-8 hours, and the mass ratio of the coating layer to the particles is 1:0.2-1:

20.

16. The method according to claim 13, characterized in that When the coating layer is a polymer coating layer, it needs to undergo carbonization treatment: heating to a carbonization temperature of 500-900°C in an inert atmosphere and keeping the temperature, then naturally cooling to room temperature, the heating rate is 1-20°C / min, and the holding time is 0.1-72h.

17. The method according to claim 1, characterized in that The transient heating method in step (4) is one of Joule heating, microwave heating, electric spark heating, plasma heating, infrared heating, combustion heating, thermal explosion heating, thin film electric heater heating and electromagnetic pulse heating.

18. The method according to claim 1, characterized in that In step (4), the temperature is raised to 800-1000°C by at least one pulse, and the heating rate is 1×10 6 -100℃ / s. After reaching the target temperature, the system enters the heat preservation stage with a heat preservation time of 0.01-200s. After the heat preservation stage, the temperature is immediately lowered to form ultrafine nanoparticles.

19. The method according to claim 1, characterized in that The cooling rate in step (4) is 1×10 6 -100℃ / s, until room temperature.

20. The method according to claim 1, characterized in that The atmosphere in the reaction zone in step (4) is a non-oxidizing atmosphere, including a low vacuum or a mixture of one or more of helium, argon and nitrogen.

21. A method for preparing ultrafine nano-silicon-based negative electrode materials based on in-situ high-temperature phase change in a specific confined microcavity, characterized in that: The method is prepared by any one of claims 1 to 20.

Citation Information

Patent Citations

  • Low-expansion silicon-carbon negative electrode material and preparation method thereof

    CN115986075A

  • Negative active material having expanded graphite and silicon fusions for lithium secondary battery, method for preparing the same and lithium secondary battery comprising thereof

    KR101855848B1

  • Multi-hierarchical composite material prepared at ultra-high temperature, and preparation method therefor and use thereof

    WO2024000823A1

  • Silicon-carbon negative electrode material, preparation method and battery

    WO2024193118A1

Cited By

  • Lithium ion battery electrode material and preparation method thereof

    CN121260767A

  • Silicon-titanium composite material and preparation method and application thereof

    CN122338045A

  • Silicon-titanium composite material, preparation method and application thereof

    CN122338045B

  • Ultrafine nano-silicon-based negative electrode material prepared on basis of in-situ high-temperature phase change in confinement microcavity, and preparation method therefor

    WO2026081918A1